Batman Arkham origins. - WB Games (Firm); DC Comics, Inc. (Burbank, CA : WB Games, 2013)
Game features an expanded Gotham City and introduces an original prequel storyline occurring several years before the events of Batman: Arkham Asylum and Batman: Arkham City. Taking place before the rise of Gotham City's most dangerous villains and assassins, the game showcases a young, raw, unrefined Batman as he faces a defining moment in his early career as a crime fighter that sets his path to becoming the Dark Knight.
Black Mask's assassins -- Prowl the streets of Gotham City -- A world of firsts -- Expand your arsenal.
Title from disc label.
1 player (network 3-8). PlayStation network compatible; DualShock 3 compatible; headset compatible; six-axis motion sensitive, headset compatible.
ESRB content rating: Teen (blood, drug reference, language, mild suggestive themes, violence).
System requirements: PlayStation 3; 4.7 GB hard drive space. Online play requires Internet connection and registered PlayStation Network account; some online features and add-on content may require additional hardware and/or fees. Blu-ray disc.
107621
Keywords: Batman -- (Fictitious character); Batman (Fictitious character) -- Computer games; Superheroes; Comic strip characters; Computer adventure games; Computer games; Video games; Computer adventure games; PlayStation 3 video games; PS3.; Sony video games